Logistics Costs Optimization to the LPG Commercialists in Azuay-Ecuador - Coronel-Pangol, Katherine Tatiana (2020)
This article aims to solve the problem of optimization of logistics costs of the Liquefied Petroleum Gas (LPG) distribution tanks in the province of Azuay, Ecuador. Hypothesis is that distributors have similar business structures and basic cost structures, so they have a margin of optimization and application of the model is adequate. Collection of information from primary source has been carried out, and later an integer programming model applied to the analyzed sector has been proposed, to respond to the optimization problem. For the resolution, the Visual Basic tools in Excel have been used, which allows to present a summary table with quantities and the optimized costs, as well as the savings value for the businesses. Among the main conclusions, an optimization of logistics costs of approximately 40% on average for the analyzed sector has been determined.